An independent association of prenatal depression with wheezing and anxiety with rhinitis in infancy. Issue 8 (22nd September 2015) - Cheng, Tuck Seng; Chen, Helen; Lee, Theresa; Teoh, Oon Hoe; Shek, Lynette P.; Lee, Bee Wah; Chee, Cornelia; Godfrey, Keith M.; Gluckman, Peter D.; Kwek, Kenneth; Saw, Seang Mei; Chong, Yap‐Seng; et al.
Abstract: Background: Different maternal psychological states during pregnancy have been associated with wheeze–rhinitis–eczema symptoms in children. However, previous studies were limited and it was unclear whether the type of prenatal psychological state was associated with a particular symptom. We examined the association of maternal depression and anxiety during pregnancy with wheeze–rhinitis–eczema symptoms in infancy. Methods: In a longitudinal birth cohort (GUSTO) of 1152 mother–child pairs, wheeze–rhinitis–eczema symptoms in the infants during the first year of life were collected by parental report. Maternal depressive and anxiety symptoms were assessed at 26 weeks of gestation using the Edinburgh Postnatal Depression Scale (EPDS) and State Trait Anxiety Inventory (STAI). Logistic regression analyses were performed with adjustment for potential confounders. Results: An increased risk of wheezing was found in infants of pregnant women with probable depression (EPDS ≥ 15) [odds ratio (OR) = 1.85 (95% confidence interval (CI) 1.10–3.12)], and an increased risk of rhinitis was associated with maternal anxiety [STAI state ≥ 41: OR = 1.42 (95% CI 1.04–1.93); STAI trait ≥ 43: OR = 1.38 (95% CI 1.01–1.88)]. After adjusting for known risk factors for the development of allergic disease, these associations remained significant [EPDS ≥ 15: adjusted OR = 2.09 (95% CI 1.05–4.19); STAI state ≥ 41: adjusted OR = 1.82 (95% CI 1.17–2.82); STAI trait ≥ 43: adjusted OR = 1.70 (95% CI 1.10–2.61)]. However, maternal psychological states were not associated with infantile eczema. Conclusion: This study suggests that there may be an independent effect of prenatal depression on wheezing and anxiety on rhinitis in infancy.